What factors influence the internationalization of Swedish Private Equity Firms – a study of four market leaders in Sweden. - Blom,Malin; Stendahl,Daniel; Kadiri Hassani,Youssef (2004)
Private equity is a relatively new and unexplored business in Sweden. The aim of our thesis is to explore the factors influencing the internationalization of Swedish private equity firms. Why do the firms chose to internationalize? To what degree are the firms internationalized? What have driven the firms to internationalize to the current extent? Furthermore we aim to map the structure of the internationalization of the different firms and understand why the Swedish private equity firms choose different levels of internationalization. The research is a qualitative case study, which best fits our purpose for an in-depth research of a fairly small amount of cases. Four Swedish private equity firms have been studied through qualitative interviews with several semi-structured questions focusing on the phenomena of internationalization. Expert interviews and other interviews have been conducted in a likely way, with the structure of a discussion where the interviewee was given great space to express his or her opinion. To get the broadest most accurate picture possible of the capital market, the risk capital issues and the internationalization, a wide range of books, articles, magazines and other sources where used. In our study, we find that the Swedish private equity firms are geographically focused on the Swedish, Nordic or Northern European market when it comes to investing in portfolio companies. Through the Internationalization Matrix we show that the following seven factors have great influence on the internationalization of Swedish private equity firms: market knowledge, past experiences, network, reputation, competition, cultural differences and social impact, having both triggering and suppressing effect on the internationalization. These internal and external influential factors form the firm’s chosen strategy, leading to internationalization. Throughout the internationalization, valuable and crucial experience is obtained and implemented in the firm changing the firm specific appearance of the influential factors.
Keywords: Private equity; internationalization; Management of enterprises; Företagsledning, management